2004
DOI: 10.1002/ajmg.a.30102
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of genetic testing for familial hypercholesterolemia within a previously aware population: A randomized controlled trial

Abstract: This trial tests the hypothesis that confirming a clinical diagnosis of familial hypercholesterolemia (FH) by finding a genetic mutation reduces patients' perceptions of control over the disease and adherence to risk-reducing behaviors. Three hundred forty-one families, comprising 341 hypercholesterolemia probands and 128 adult relatives, were randomized to one of two groups: (a) routine clinical diagnosis; (b) routine clinical diagnosis plus genetic testing (mutation searching in probands and direct gene test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
204
5
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 31 publications
8
204
5
1
Order By: Relevance
“…In familial hypercholesterolemia, it was found that information about genetic backgrounds can reduce the beliefs that diets might be helpful. 7 The results of our study show that obese people highly appreciate a general consultation, and the additional inclusion of genetic information can lead to new insights about weight problem. This suggests that genetic information about obesity is well-received.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In familial hypercholesterolemia, it was found that information about genetic backgrounds can reduce the beliefs that diets might be helpful. 7 The results of our study show that obese people highly appreciate a general consultation, and the additional inclusion of genetic information can lead to new insights about weight problem. This suggests that genetic information about obesity is well-received.…”
Section: Discussionmentioning
confidence: 70%
“…For familial hypercholesterolemia, it was shown that finding a mutation had no impact on perceived control over the disease, but participants believed less strongly in the efficacy of diet in reducing their cholesterol level. 7 Thus, knowing about the genetic etiology influenced the beliefs and motivation for behavior change.…”
mentioning
confidence: 99%
“…DNA cascade screening is increasingly becoming the preferred approach for identifying FH in asymptomatic individuals, within the UK and across Europe (Leren 2004;Finnie 2010); however, as Marteau et al (2004) note, relatively little is known about the impact on participants, particularly those initiating the familial cascade. The recent introduction of DNA cascade screening for FH in Scotland, therefore, has provided an important and timely opportunity to explore index patients' views of this service.…”
Section: Discussionmentioning
confidence: 99%
“…While questions have been raised about the most efficient way of implementing familial cascading for FH (Marteau et al 2004;Minhas et al 2009), limited attention has been paid to index patients' preferences for different cascading methods. Some research suggests that direct cascading is perceived as acceptable to members of the public (Tonstad et al 1995) and family members (van Maarle et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators found that those who had the mutations believed less strongly in the efficacy of diet in reducing cholesterol levels (P = 0·02) and demonstrated a trend in believing more strongly in the efficacy of cholesterol-lowering medication (P = 0·06). Therefore, the authors concluded that genetic testing does not affect the extent to which individuals believe that they have control over their health, but does affect their perceptions of how control is most effectively obtained (23) . Hollands et al investigated the effect of communicating risk assessment for Crohn's disease based on genotype on motivating smoking cessation for 24 h or longer, assessed at 6 months (24) .…”
Section: Studies Investigating the Impact Of Direct-to-consumer Testingmentioning
confidence: 99%